2011
DOI: 10.1167/iovs.10-5737
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Multifocal Pupillographic Objective Perimetry in Glaucoma

Abstract: mfPOP produces separate information on response delay and afferent and efferent defects at every point in the field. The diagnostic accuracy of the 40-region, 150-ms stimulus is comparable to that of commonly used subjective perimeters and encourages further investigation of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 39 publications
5
52
0
1
Order By: Relevance
“…However, a more advanced device that would readily allow for such testing is in development, and extensive testing on prototypes has been published. 48,49 Once available, such testing methods may help better define actual functional visual disability and more accurately reflect the functional efficacy of current ocular and future CNS-oriented therapeutic approaches, even in patients with relatively mild disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more advanced device that would readily allow for such testing is in development, and extensive testing on prototypes has been published. 48,49 Once available, such testing methods may help better define actual functional visual disability and more accurately reflect the functional efficacy of current ocular and future CNS-oriented therapeutic approaches, even in patients with relatively mild disease.…”
Section: Discussionmentioning
confidence: 99%
“…Individual stimuli were presented for 33 ms. For these transient stimuli, the response amplitudes are related to the stimulus luminance and the mean interval between presentations. 15,16,[21][22][23] The mean intervals between presentation of stimuli at one location were 0.25, 1 and 4 s ( Table 3) making four different stimulus protocols. The protocol names reflect the differing features of the number of regions/field and the mean presentation interval per region in seconds.…”
Section: Stimulimentioning
confidence: 99%
“…This group has been investigating mfPOP methods combining concurrent independent assessment of both visual fields and sparse stimulation, 13 providing recording times of 2 to 3 min/eye. Those methods have been demonstrated to have diagnostic value in glaucoma, [14][15][16] early-stage diabetic retinopathy, 17 and age-related macular degeneration. [18][19][20] Aside from the 60 degree-wide stimuli used in most of those studies, mfPOP stimuli for the central retina have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der Test ist kurz, wenig belastend und nur gering von einer Fehlrefraktion oder einer Linsentrübung abhängig[3]. Die bisherigen Ergebnisse ermutigen zur Weiterentwicklung dieser Methode (u. a. Normwertdefinition, Feinabstimmung von Stimuluseigenschaften).…”
unclassified